Physico-chemical characteristic of gorewada lake water in Nagpur, India - ., Salahuddin (SPC Journal of Environmental Sciences, 2021)
Â The proper control and appraisal of lake water condition and its purification is very crucial for appropriate care and management purposes. Water quality checking and investigation of the Gorewada Lake was implemented for numerous physico-chemical parameters in the month of June, 2016.These components are: (i) pH, (ii) Temperature, (iii) Electric Conductivity, (iv) Dissolved Oxygen, (v) Biochemical Oxygen Demand, (vi) Chemical Oxygen Demand, (vii) Total Phosphorous, (viii) Suspended Solid (ix) and Total Nitrogen respectively. The lake water is not suitable for drinking, bathing and other life supporting activity.Â Â